MODELING OF SPATIAL DISTRIBUTION OF SPEEDS OF METAL IN MOLDS WITH VARIOUS TYPE OF CONNECTION OF GATING CHANNELS IN CAE «PROLIT-І» - A. N. Chichko; V. F. Sobolev; S. G. Lihouzov; o A. Sachek; O. I. Chichko (Литьë и металлургия)
The mathematical apparatus for the calculation analysis of the metal current process in casting mold cavities is described. Boundary conditions for calculation of highspeed regimes and time of filling with metal of complex in the dimensional respect moulds are developed.